DESAIN KEBIJAKAN PEMBAYARAN JASA LINGKUNGAN SEBAGAI ALTERNATIF UNTUK PEMBANGUNAN PARIWISATA BERKELANJUTAN DI PULAU KECIL : STUDI KASUS DI KABUPATEN LOMBOK UTARA - Diswandi, Diswandi; Afifi, Mansur; Busaini, Busaini; Fadliyanti, Luluk; Dakwah, Muhammad Mujahid (Universitas Mataram, 2024)
The tourism industries on small islands frequently prioritize economic gains, while the environmental consequences of these activities, which include the impact on the ecosystem, are typically overlooked due to insufficient consideration of conservation costs. If this pattern persists, the marine parks in the region may eventually lose their appeal and adversely affect the tourism industry. The Payment for Ecosystem Services (PES) program offers a potential avenue for executing conservation fundraising initiatives by leveraging contributions from travelers and tourism enterprises. This study employs a qualitative methodology to analyze public policies pertaining to the implementation of the PES program in Gili Matra. The study concluded that it is feasible to establish PES (Payment for Ecosystem Services) programs on Gili Matra through mandatory initiatives, with the aim of fostering a sustainable tourism sector.